(5t-6c+4)+(-8t+9c)=

Simple and best practice solution for (5t-6c+4)+(-8t+9c)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (5t-6c+4)+(-8t+9c)= equation:


Simplifying
(5t + -6c + 4) + (-8t + 9c) = 0

Reorder the terms:
(4 + -6c + 5t) + (-8t + 9c) = 0

Remove parenthesis around (4 + -6c + 5t)
4 + -6c + 5t + (-8t + 9c) = 0

Reorder the terms:
4 + -6c + 5t + (9c + -8t) = 0

Remove parenthesis around (9c + -8t)
4 + -6c + 5t + 9c + -8t = 0

Reorder the terms:
4 + -6c + 9c + 5t + -8t = 0

Combine like terms: -6c + 9c = 3c
4 + 3c + 5t + -8t = 0

Combine like terms: 5t + -8t = -3t
4 + 3c + -3t = 0

Solving
4 + 3c + -3t = 0

Solving for variable 'c'.

Move all terms containing c to the left, all other terms to the right.

Add '-4' to each side of the equation.
4 + 3c + -4 + -3t = 0 + -4

Reorder the terms:
4 + -4 + 3c + -3t = 0 + -4

Combine like terms: 4 + -4 = 0
0 + 3c + -3t = 0 + -4
3c + -3t = 0 + -4

Combine like terms: 0 + -4 = -4
3c + -3t = -4

Add '3t' to each side of the equation.
3c + -3t + 3t = -4 + 3t

Combine like terms: -3t + 3t = 0
3c + 0 = -4 + 3t
3c = -4 + 3t

Divide each side by '3'.
c = -1.333333333 + t

Simplifying
c = -1.333333333 + t

See similar equations:

| 6(1/4)= | | 3x-[-2-4x]= | | 16x-14=616 | | 4w-2t=10 | | 2.9q-2.1-5.4=-1.5q-2.1 | | x-3y+2z=16 | | 10+23-x=180 | | 8h+3(4h-6)= | | -1thirds=7 | | 7x+15=512x | | (-2n^3+8n^2+6)+(4n^3-7n^2)= | | -14x^2-50x+24= | | -2x+2x-5=-5 | | 12-21z= | | A+3a=12 | | 21/2+x+18=306 | | 10y=5x-6 | | -1/4+8= | | 3x(x+1)=12 | | 9d-28=4d-3 | | 9x-x^2=6 | | 8=5-7p^2+10p | | -2x+8=6-2X | | x*-3x-10=0 | | x+8=6-2x | | 3x-2y+3z=-4 | | (4n^3-4n)+(3n^3+7n+8)= | | 2x-y+z=-1 | | 17=-2*x+3 | | 3(7z-4)= | | 25k^2+30k+9=0 | | 125*5-25+10= |

Equations solver categories